Trends in Interventional Physiology: A Journey Towards Future Innovations - Samreen Farooqui; Keerthana; Vijaya Lakshmi; Meghna Poonia; Jitendra Patel (Medical Science: Trends and Innovations Vol. 11, 2025)
Interventional physiology is the division of physiology, which applies interventional techniques or procedures to diagnose and treat a variety of medical conditions. There have been significant technological developments and clinical revolutions in recent times that characterized the current advancement in interventional physiology. In recent years, the field of interventional physiology has made unlimited progress from its borderline position within medicine to become one of the leading domains in medical science. This book chapter presents a comprehensive analysis of the transformative journey of interventional physiology by outlining its latest breakthroughs, emerging trends, and likely future directions. Relating to numerous recent studies, this piece highlights different technological advancements and clinical practice changes that are currently affecting patient care. Taking into account the most recent research findings, this book chapter provides an all-encompassing view of the status and future path of interventional physiology.